Front Cover: Effect of Chelate Ring Size of Binuclear Copper(II) Complexes on Catecholase Activity and DNA Cleavage (Eur. J. Inorg. Chem. 18/2021). Issue 18 (27th April 2021) - Homrich, Alana M.; Farias, Giliandro; Amorim, Suélen M.; Xavier, Fernando R.; Gariani, Rogério A.; Neves, Ademir; Terenzi, Hernán; Peralta, Rosely A.
Abstract : The Front Cover illustrates the dual‐functional application of the new bioinspired dinuclear copper(II) complex. On the one hand, it mimics the function of the enzyme catechol oxidase, responsible for the browning process of fruits and plants. On the other, it acts as artificial nuclease, capable of producing fragments in the DNA, similar to those formed by restriction enzymes. Associated with these applications, the effect of chelate ring size of complexes on catecholase activity and DNA cleavage was evaluated, revealing that the changes in the soft side contributed positively to the activity in both cases. More information can be found in the Full Paper by R. A. Peralta and co‐workers .